1995
DOI: 10.1038/hdy.1995.126
|View full text |Cite
|
Sign up to set email alerts
|

Inherited stress resistance and longevity: a stress theory of ageing

Abstract: Ageing is considered in the context of the abiotic stresses to which free-living organisms are normally exposed. Assuming that the primary target of selection of stress is at the level of energy carriers, trade-offs under the rate-of-living theory of ageing predict increased longevity from selection for stress resistance. Changes in longevity then become incidental to selection for stress resistance. I therefore suggest the reformulation of the rate-of-living theory to become a stress theoiy of ageing. This di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 55 publications
3
32
1
Order By: Relevance
“…Moreover, studies performed on Drosophila indicate that the protective effect of heat hardening is sustained long after Hsp70 expression returns to prestress level (Krebs and Feder 1997;Dahlgaard et al 1998), suggesting that factors other than Hsps may contribute to protection against heat. Indications of connections between stress in general and low metabolic rate (Hoffmann and Parsons 1991) and the stress theory of aging (Parsons 1995) support this view, and it is thus likely that genes involved in basal and induced heat resistance are not necessarily the same. (Tusher et al 2001) for all genes on the array.…”
Section: Introductionmentioning
confidence: 71%
“…Moreover, studies performed on Drosophila indicate that the protective effect of heat hardening is sustained long after Hsp70 expression returns to prestress level (Krebs and Feder 1997;Dahlgaard et al 1998), suggesting that factors other than Hsps may contribute to protection against heat. Indications of connections between stress in general and low metabolic rate (Hoffmann and Parsons 1991) and the stress theory of aging (Parsons 1995) support this view, and it is thus likely that genes involved in basal and induced heat resistance are not necessarily the same. (Tusher et al 2001) for all genes on the array.…”
Section: Introductionmentioning
confidence: 71%
“…Previous studies in Drosophila have shown that flies selected for increased stress resistance have longer lifespans. 36,37 Furthermore, this increased resistance to stress is positively correlated with lipid and water content. 38,39 We, therefore, tested green tea's ability to increase stress resistance.…”
Section: Gtps Protect Against Iron Toxicitymentioning
confidence: 96%
“…Hormesis is the adaptive response to small harmless doses of a potentially fatal environmental or intrinsic stress stimulus, which renders the organism resistant to increased doses of this particular stressor. The signalling pathways that mediate resistance or adaptation to stress are also involved in longevity and have been already introduced in previous chapters (Calabrese et al, 2011;Johnson et al, 2002;Parsons, 1995). In this part of the review, we highlight autophagy as an integral component of several stress response mechanisms, which represents a conserved stress coping strategy in eukaryotes.…”
Section: Environmental/cellular Stress Signals Induce Autophagy-mediamentioning
confidence: 96%